Aspects of the privatization of religiosity during a pandemic = Oblicza prywatyzacji religijności w czasie pandemii - Ciesielski, Remigiusz (Przegla̜d religioznawczy, 2021)
The text presents the reaction of Catholics to the decisions of Polish bishops regarding the provisions of state law in the face of the pandemic. Using the results of his research, the author includes these behaviours in secularization and privatization of religion. He calls the results of his research the privatization of religiosity.